IDENTIFIKASI SEBAB-SEBAB KERUSAKAN OPRIT JEMBATAN DAN ALTERNATIF PENANGANANNYA (Studi Kasus: Jembatan Nambo-Bungkutoko Kota Kendari) - Subhan A.K., Muh.; Christady H., Hary; Triwiyono, Andreas (Civil Engineering Forum Teknik Sipil, 2007)
Nambo–Bungkutoko bridges have had damages at the retaining walls and the piles of soil in bridge ramp clearly marked by the cracks of retaining walls and the deforming piles of soil in the bridge ramp. The structure of retaining walls of soil comprises the stone formations of 44,15 m in distance from Nambo and 40 m from Bungkutoko with various heights of retaining walls ranging from 4,22 m to 8,50 m from Nambo bridge ramp and 4,50 m to 8,20 m from Bungkutoko bridge ramp. To identify the causes of damage, analysis is conducted using Plaxis Program version 7.2. The amount of models analyzed is 9 consisted of 4 for Nambo ramp and 5 for Bungkutoko ramp. From the result sondir test, the type, depth, and properties of soil can be known, i.e. the depth of 0-2 m is soft clay, of 2-4 m clay, of 4-6 m loosen sand, and of 6-10 m solid sand. Whereas to know the solidness of soil in field, the proctor test is modified at damaged locations, each of 2 points and the results the solidness of Nambo ramp of point 01 is 8.01%, and of point 02 84.19%, while that of Bungkutoko ramp of point 03 is 82.68% and of point 04 87.05%. In providing the alternative handling of the ramp on 3 alternative is node to node anchor, bronjong and counterweight The result of the plaxis program is that at the Nambo ramp, the safety factor of STA 0+24,15 is 1.120 and that of STA 0+44,15 is 1.000, while at the Bungkutoko ramp, that of STA 0+25 is 1.169 and that of STA 0+40 is 1.000. A counterweight is chosen caused total, vertical and horizontal displacement is small and safety factor to high then as a result, at the Nambo ramp, the safety factor of STA 0+24,15 is 1.664 and that of STA 0+44,15 is 1.196, while at the Bungkutoko ramp, that of STA 0+25 is 1.694 and that of STA 0+40 is 1.208. Costs needed for all the rehabilitations of the bridge ramp with the counterweight is Rp 467.210.211